2022
DOI: 10.3389/fcell.2021.822315
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA-Seq Reveals the Promoting Role of Ferroptosis Tendency During Lung Adenocarcinoma EMT Progression

Abstract: Epithelial-mesenchymal transition (EMT) and ferroptosis are two important processes in biology. In tumor cells, they are intimately linked. We used single-cell RNA sequencing to investigate the regulatory connection between EMT and ferroptosis tendency in LUAD epithelial cells. We used Seurat to construct the expression matrix using the GEO dataset GSE131907 and extract epithelial cells. We found a positive correlation between the trends of EMT and ferroptosis tendency. Then we used SCENIC to analyze different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 73 publications
(88 reference statements)
0
19
0
Order By: Relevance
“…The growth factor HBEGF, which is highly expressed in Monocytes, Neutrophils, Dendritic Cells, GMP Cells, Macrophages, and various Epithelial Cells, interacts with CD9 expressed in Cancer Cells to help mediate tumorigenesis and proliferation [38]. We also found that Cancer Cells interact with ITGB1, highly expressed in multiple cells such as Fibroblasts, Endothelial Cells, and Basal Cells, through angiogenesis signal molecules (VEGFA) to stimulate tumor growth and metastasis [39]. This discovery provides a new research idea for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 90%
“…The growth factor HBEGF, which is highly expressed in Monocytes, Neutrophils, Dendritic Cells, GMP Cells, Macrophages, and various Epithelial Cells, interacts with CD9 expressed in Cancer Cells to help mediate tumorigenesis and proliferation [38]. We also found that Cancer Cells interact with ITGB1, highly expressed in multiple cells such as Fibroblasts, Endothelial Cells, and Basal Cells, through angiogenesis signal molecules (VEGFA) to stimulate tumor growth and metastasis [39]. This discovery provides a new research idea for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 90%
“…The growth factor HBEGF, which is highly expressed in Monocytes, Neutrophils, Dendritic Cells, GMP Cells, Macrophages, and various Epithelial Cells, interacts with CD9 expressed in Cancer Cells to help mediate tumorigenesis and proliferation [34]. We also found that Cancer Cells interact with ITGB1, highly expressed in multiple cells such as Fibroblasts, Endothelial Cells, and Basal Cells, through angiogenesis signal molecules (VEGFA) to stimulate tumor growth and metastasis [35]. This discovery provides a new research idea for tumor immunotherapy.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast to the protective effect in NAFLD, the published study has shown that SCP2 can promote the accumulation of low-density lipoprotein cholesterol (LDL-C) and reduce high-density lipoprotein cholesterol (HDL-C), promoting the development of atherosclerosis and hyperlipidemia [28]. And previous studies have indicated that SCP2 can inhibit ferroptosis poisoning inhibitors (GPX4 and cav1) and promote other ferroptosis poisoning drivers (PRKAA1, PRKAA2) [29]. MUC1 is a large O-type glycoprotein that is essential to maintain the function of epithelial cell surface [30].…”
Section: Discussionmentioning
confidence: 99%